A cross-sectional study of etiology, clinical profile, prognosis and outcome of acute kidney injury in a tertiary care hospital - Yafas Nazir Khan; Mansi; Rolanda Saint Louis; Shehla Ashraf; Purna Chand Paidi (International Journal of Research in Medical Sciences, 2026)
Background: Acute kidney injury (AKI) is a common and serious clinical condition associated with significant morbidity, mortality, prolonged hospital stay, and increased healthcare burden. Early identification of etiological factors and severity is essential for timely intervention and improved outcomes. Methods: A hospital-based analytical cross-sectional study was conducted among 150 patients with AKI admitted to a tertiary care hospital over 18 months. Patients fulfilling acute kidney injury network (AKIN) diagnostic criteria were included. Demographic characteristics, clinical profile, urine output, etiological factors, AKI type, AKIN stage, treatment modalities, and outcomes were recorded. Relevant laboratory investigations and imaging studies were performed, and data were analyzed using descriptive statistics. Results: The mean age of participants was 43.96 years, with a male predominance. Oliguria was the most common clinical presentation. Sepsis was the leading etiological factor, followed by poisoning and snake bite. Intrinsic renal AKI was the predominant type, while post-renal AKI was uncommon. Most patients presented with AKIN stage 3 disease. Conservative management was sufficient for many patients, whereas others required hemodialysis. Recovery was observed in the majority of patients, although mortality remained higher among those with severe AKI and associated systemic illness. Conclusions: Sepsis, poisoning, and snake bite were the major contributors to AKI in the study population. Early diagnosis, prompt identification of the underlying etiology, timely treatment, and appropriate renal replacement therapy are essential for improving clinical outcomes and reducing AKI-related mortality.